Iron deficiency parameters in autism spectrum disorder: clinical correlates and associated factors - Serkan Gunes; Ozalp Ekinci; Tanju Celik (BMC, 2017)
Abstract Background High prevalence of iron deficiency (ID) and iron deficiency anemia (IDA) has been reported in children with autism spectrum disorder (ASD). However, there is a limited number of studies about the association between iron deficiency parameters and clinical symptoms of ASD. This study aims to compare hemoglobin, hematocrit, iron, ferritin, MCV, and RDW levels between ASD patients and healthy controls and to investigate the correlation between these values and clinical symptoms of ASD. Methods The sample consisted of 100 children in ASD patient group and 100 healthy controls, with an age range of 2-18 years. We used ferritin cutoff of < 10 ng/mL for preschoolers (< 6 years) and < 12 ng/mL for school-aged (> 6 years) children to evaluate ID. Anemia was defined as hemoglobin < 11.0 g/dL for preschoolers and < 12.0 g/dL for school-aged children. Childhood Autism Rating Scale (CARS), Autism Behavior Checklist (AuBC), and Aberrant Behavior Checklist (AbBC) were used to evaluate the severity of autistic symptoms and behavioral problems. Categorical variables were compared by using chi-square test. Normally distributed parametric variables were compared between groups by using Independent Samples t test. Pearson's correlation analysis was used in order to examine the correlations. The p value < 0.05 was accepted to be statistically significant. Results Hemoglobin, hematocrit, iron, and MCV (p < 0.05) levels of children with ASD were lower than healthy controls. Hemoglobin, hematocrit, and MCV (p < 0.05) levels were found to be significantly lower in preschool ASD patients. Hemoglobin and hematocrit (p < 0.05) levels were significantly lower in ASD patients with intellectual disability. Hemoglobin (p < 0.05) levels were lower in patients with severe ASD. There was a significant negative correlation between hematocrit levels of children with ASD and CARS, AuBC, and AbBC total scores (p < 0.05). Conclusions Hemoglobin levels of children with ASD were lower than healthy children, but this was not sufficient to result in anemia. IDA in children with ASD might be associated with intellectual disability instead of ASD symptom severity.